THE EFFECT OF PROVIDING HEALTH EDUCATION USING SIMULATION MODEL TOWARD THE IMPLEMENTATION OF HAND WASHING WITH SOAP TO EARLY CHILDHOOD EDUCATION PRESCHOOL AT TUNAS MELATI KINDERGARTEN SANGGAU - Balsia, Yohanes Fredy Oskie (Universitas Tanjungpura, 2023)
Background : golden age are the preschool children who are in the age range around 3